Negative electrode material, negative electrode plate and secondary battery
By filling amorphous carbon into the negative electrode material and adjusting its particle hardness, elastic modulus and tableting orientation, the problems of low first Coulombic efficiency and insufficient cycle stability of the negative electrode material during the charge and discharge process are solved, achieving efficient and stable Lithium-ion battery performance.
Patent Information
- Application Number
- CN202411850897.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-16
AI Technical Summary
In the prior art, the negative electrode material has problems of low Coulomb efficiency and insufficient cycle stability during the charging and discharging process.
A negative electrode material is provided, which includes natural graphite and amorphous carbon filled in the pores of the natural graphite. The particle hardness of the negative electrode material is 0.28GPa~0.4GPa, the elastic modulus is 7.0GPa~8.0GPa, and the tableting orientation OI value is y ,4
By improving the densification and structural stability of the anode material and homogenizing the diffusion of lithium ions, the electrochemical performance and cycle stability of the anode material are significantly improved, making the first Coulombic efficiency ≥94% and the capacity retention rate ≥ after 400 cycles. 92.5%.
Smart Images

Figure CN119340376A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a negative electrode material, a negative electrode sheet and a secondary battery. Background Art
[0002] Lithium-ion batteries are widely used in 3C, power devices, energy storage equipment and other fields due to their advantages such as low self-discharge rate, high charge and discharge efficiency, no memory effect, and long cycle life. Negative electrode materials are an important component of lithium-ion batteries, and their performance directly affects the electrochemical performance of lithium-ion batteries. Natural graphite negative electrode materials have attracted widespread attention due to their advantages such as high specific capacity, low charge and discharge platform, and low cost. However, natural graphite has high anisotropy and internal defects. Solvent co-embedding is prone to occur during lithium ion embedding, resulting in reduced stability of the SEI film, consumption of additional lithium ions, and reduced first coulomb efficiency; and this high defect will cause graphite to undergo uneven volume expansion. During the long cycle of lithium-ion batteries, the continuous expansion and contraction of the graphite structure may lead to further expansion of the defect area, and even cause the graphite layer to fall off and cracks to form, causing long-term cycle capacity decay. Summary of the invention
[0003] The main purpose of the present invention is to provide a negative electrode material, a negative electrode sheet and a secondary battery to solve the problems of low initial coulombic efficiency and insufficient cycle stability of negative electrode materials in the prior art during the charge and discharge process.
[0004] In order to achieve the above object, according to one aspect of the present invention, a negative electrode material is provided, the negative electrode material comprises natural graphite and amorphous carbon filled in the pores of natural graphite; the particle hardness of the negative electrode material is 0.28GPa~0.4GPa, and the elastic modulus is 7.0GPa~8.0GPa; when the compaction density of the negative electrode material is 1.5~2.0g / cm 3 , the OI value of the negative electrode material's tablet orientation is y, 4<y≤11.
[0005] Furthermore, the OI value of the negative electrode material at different tableting densities is y, satisfying: y 1 ≤y≤y 2 ;
[0006] Among them, y 1 =5.46x-3.78,y 2 =8.9x-7.76, 1.5≤x≤2.0, x is the value corresponding to the compaction density of the negative electrode material.
[0007] Furthermore, when the compaction density of the negative electrode material is 1.5-2.0 g / cm 3 , the OI value of the negative electrode material's tablet orientation is 5~10.
[0008] Furthermore, the negative electrode material satisfies at least one of the following characteristics:
[0009] (1) The sphericity Sh(90%) of the negative electrode material is 0.90~0.95;
[0010] (2) The D50 volume average particle size of the negative electrode material is 8~18μm;
[0011] (3) The average particle size of the negative electrode material is 10~20μm.
[0012] Furthermore, the shape coefficient of the negative electrode material is φ, the sphericity of the particles is Sh(90%), satisfying: Δ=|φ- Sh(90%)|, and Δ≤0.08; wherein φ=D1 / D2, D1 is the D50 volume average particle size of the negative electrode material, in μm; and D2 is the equal volume average particle size of the negative electrode material, in μm.
[0013] Furthermore, the specific surface area of the negative electrode material is 2~5m 2 / g.
[0014] Furthermore, the tap density of the negative electrode material is 0.9~1.3g / cm 3 .
[0015] Furthermore, the compacted density of the negative electrode material powder is 1.7~2.0g / cm 3 .
[0016] A second aspect of the present invention provides a negative electrode sheet, which includes the negative electrode material provided by the first aspect.
[0017] A third aspect of the present invention provides a secondary battery, wherein the secondary battery comprises the negative electrode sheet provided by the second aspect.
[0018] By applying the technical solution of the present invention, the densification degree of the negative electrode material is improved, the anisotropy of the negative electrode material can be reduced, and the diffusion of lithium ions in different directions is more uniform, which helps to improve the electrochemical performance of the negative electrode material; at the same time, by limiting the particle hardness of the negative electrode material to 0.28GPa~0.4GPa, the elastic modulus to 7.0GPa~8.0GPa, and the tablet orientation OI value to y, 4<y≤11, the structural stability of the negative electrode material can be enhanced, the volume expansion can be effectively controlled, and the structural stability of the negative electrode material can be maintained during the charge and discharge process. At the same time, it is ensured that the surface and the interior of the negative electrode material have unobstructed lithium ion channels, reducing the problems of sheet shedding and crack formation, thereby improving the cycle stability. The negative electrode material is applied to secondary batteries, and the first coulomb efficiency can be ≥94%, and the capacity retention rate after 400 cycles can be ≥92.5%. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a SEM image of the negative electrode material in Example 1 of the present invention;
[0020] Figure 2 A coordinate diagram of OI values of tableting orientation of negative electrode materials at different compaction densities in the embodiments of the present invention and the comparative examples;
[0021] Figure 3 A schematic diagram of the structure of a secondary battery provided in one embodiment of the present invention during charging;
[0022] Figure 4 A schematic diagram of the structure of a secondary battery during discharge provided by one embodiment of the present invention.
[0023] Description of reference numerals:
[0024] 100 - electrode assembly; 101 - positive electrode sheet; 102 - negative electrode sheet; 103 - isolation membrane. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0026] As described in the background of the present invention, the prior art negative electrode materials have the problems of low initial coulombic efficiency and insufficient cycle stability during the charge and discharge process. In order to solve the above problems, in a typical embodiment of the present invention, a negative electrode material is provided, the negative electrode material includes natural graphite and amorphous carbon filled in the pores of natural graphite; the particle hardness of the negative electrode material is 0.28GPa~0.4GPa, and the elastic modulus is 7.0GPa~8.0GPa; when the compaction density of the negative electrode material is 1.5~2.0g / cm 3 , the OI value of the negative electrode material's tablet orientation is y, 4<y≤11.
[0027] The negative electrode material includes natural graphite and amorphous carbon filled in the pores of natural graphite, which improves the density of the negative electrode material. At the same time, since amorphous carbon is highly disordered, the filling of amorphous carbon can reduce the anisotropy of the negative electrode material, making the diffusion of lithium ions in different directions more uniform, which helps to improve the electrochemical performance of the negative electrode material.
[0028] The particle hardness and elastic modulus of the negative electrode material are crucial to the electrochemical performance and cycle stability of the secondary battery, and can also reflect the degree of internal densification of the particles and the degree of amorphous carbon filling. Among them, the particle hardness (HIT) of the negative electrode material directly reflects the ability of the graphite particles to resist elastic deformation and plastic deformation under external forces. The elastic modulus (EIT) of the negative electrode material reflects the ability of the negative electrode material to resist external forces during the elastic deformation stage, that is, the stress required for the material to produce unit strain when subjected to force.
[0029] The particle hardness of the negative electrode material will affect its volume expansion and contraction. By limiting the particle hardness of the negative electrode material to 0.28GPa~0.4GPa, the graphite particles have sufficient mechanical strength to withstand the volume expansion and contraction generated during the insertion and extraction of lithium ions, that is, they can better resist the mechanical stress in this process, which helps to reduce the fragmentation and shedding of particles during the cycle, thereby improving the cycle stability; secondly, it helps to limit the expansion of the pores inside the particles, reducing the probability of electrolyte solvent molecules and lithium ions being co-embedded in the graphite layer, thereby reducing the excessive consumption of the SEI film and improving the first coulomb efficiency; in addition, during the charge and discharge cycle of the secondary battery, the graphite particles undergo repeated volume changes. When the particle hardness is 0.28GPa~0.4GPa, it helps to maintain the structural integrity of the negative electrode material, reduce the capacity attenuation caused by mechanical wear and structural damage, and extend the service life of the secondary battery.
[0030] The elastic modulus of the negative electrode material is related to its stress-strain properties. By limiting the elastic modulus of the negative electrode material to 7.0GPa~8.0GPa, it is shown that the elastic deformation of the negative electrode material during the lithium ion insertion and deinsertion process can be well controlled, so that the volume change of the negative electrode material during the cycle is effectively alleviated, and it can better adapt to the volume change, reduce cracks and particle shedding caused by stress concentration, and help improve the cycle stability; secondly, it helps to stabilize the SEI film during the charge and discharge cycle, reduce the film rupture caused by material expansion, thereby improving the first coulomb efficiency and cycle performance; in addition, the elastic modulus is related to the diffusion dynamics of lithium ions in the negative electrode material. The appropriate elastic modulus means that the stress inside the material is lower and the diffusion path of lithium ions is smoother, which helps to increase the transmission rate of lithium ions, thereby improving the electrochemical properties of the secondary battery, such as charge and discharge rate and capacity.
[0031] The negative electrode material has diffraction peaks on the (004) crystal plane and the (110) crystal plane in the X-ray diffraction spectrum, and the OI value of the negative electrode material is the ratio of the diffraction peak area of the pressed sheet formed by the negative electrode material on the (004) crystal plane to the diffraction peak area of the (110) crystal plane. In some embodiments, when the compaction density of the negative electrode material is 1.5-2.0 g / cm 3, the OI value of the tablet orientation of the negative electrode material is y, 4<y≤11. The OI value of the tablet orientation is a parameter that describes the order of the graphite sheet arrangement in the negative electrode material. By limiting the OI value of the tablet orientation to y, 4<y≤11, it helps to improve the kinetic properties of the material. Since amorphous carbon is highly disordered, the filling of amorphous carbon can reduce the OI value of the tablet orientation. This disorder helps prevent the solvent in the electrolyte from being co-embedded in the graphite layer, thereby improving the interfacial transport kinetics of lithium ions. The present invention helps to improve the first coulombic efficiency and cycle stability of the negative electrode material by limiting the OI value of the tablet orientation within the above range.
[0032] The present invention limits the particle hardness of the negative electrode material to 0.28GPa~0.4GPa, the elastic modulus to 7.0GPa~8.0GPa, and the tablet orientation OI value to y, 4<y≤11, which can not only reflect the high degree of internal densification of the particles and the high degree of amorphous carbon filling, but also achieve a balance between structural stability and lithium ion transfer kinetics, taking into account the improvement of the first coulomb efficiency and cycle stability. Specifically, on the one hand, the structural integrity of the negative electrode material during the cycle is guaranteed, thereby improving the cycle stability; on the other hand, the diffusion path of lithium ions in the negative electrode material is optimized, which is conducive to improving electrochemical performance, such as the first coulomb efficiency. This synergistic effect helps the negative electrode material maintain moderate elastic deformation during the lithium ion insertion and deinsertion process, avoid excessive plastic deformation, maintain a more stable SEI film and better electrochemical performance, thereby taking into account the improvement of the first coulomb efficiency and cycle stability.
[0033] The particle hardness and elastic modulus of the negative electrode material can be determined by an indentation hardness test, for example, a nanoindenter can be used for measurement. During the test, a hard indenter is pressed into the particle surface with a certain force and then unloaded. The hardness value of the negative electrode material is calculated by measuring the depth and width of the indentation, as well as the magnitude of the applied force. The elastic modulus is calculated by measuring the unloading process of the indentation on the surface of the material. At least 10 particles are tested for each sample, and the average values of the hardness value and elastic modulus are taken after the test, that is, the particle hardness and elastic modulus of the negative electrode material.
[0034] According to the research of the present invention, the above-mentioned negative electrode material is applied to the secondary battery, which can significantly improve the first coulomb efficiency and cycle stability. This is because, on the one hand, due to the amorphous carbon in the natural graphite pores in the negative electrode material of the present application, the densification degree of the negative electrode material is improved, the anisotropy of the negative electrode material can be reduced, and the diffusion of lithium ions in different directions is more uniform, which helps to improve the electrochemical performance of the negative electrode material; on the other hand, by limiting the particle hardness of the negative electrode material to 0.28GPa~0.4GPa, the elastic modulus is limited to 7.0GPa~8.0GPa, and the tablet orientation OI value is y, 4<y≤11, which not only indicates that the internal density of the particles is high, the amorphous carbon filling degree is high, and the negative electrode material has appropriate mechanical strength and deformation capacity, which can resist the volume change during the charge and discharge process, and optimize the transmission dynamics of lithium ions, thereby improving the stability of the SEI film and the overall performance of the secondary battery. Applying this negative electrode material to secondary batteries can make the initial coulombic efficiency ≥94% and the capacity retention rate ≥92.5% after 400 cycles, which helps to obtain more efficient, stable and long-life secondary batteries.
[0035] In some preferred embodiments, the tableting orientation OI value y of the negative electrode material at different tableting densities satisfies: y 1 ≤y≤y 2 ; Among them, y 1 =5.46x-3.78,y 2 =8.9x-7.76, 1.5≤x≤2.0, x is the value corresponding to the compaction density of the negative electrode material; y 2 With y 1 They are the upper and lower limits of the OI value of the tablet orientation under different compaction densities. By limiting the OI value of the tablet orientation of the negative electrode material and the tablet compaction density to meet the above requirements, the isotropy of the negative electrode material can be ensured to be high, the polarization effect during charging can be ensured to be small, the volume effect can be limited, and the formation of new SEI can be reduced. In addition to further improving the first coulombic efficiency and cycle stability, it can also maximize the capacity, thereby taking into account the improvement of the first coulombic efficiency, capacity and cycle stability of the negative electrode material.
[0036] Specifically, when the compaction density of the negative electrode material is 1.5 g / cm 3 , that is, when x is 1.5, y 1 =4.41,y 2 =5.59, at this time, 4.41≤y≤5.59, the tablet orientation OI value is 4.41~5.59; when the tablet compaction density of the negative electrode material is 2g / cm 3 , that is, when x is 2, y 1 =7.14,y 2=10.04, at this time, 7.14≤y≤10.04, the tablet orientation OI value is 7.14~10.04, and so on. In the specific implementation of the present invention, the tablet compaction density of the negative electrode material substantially refers to the compaction density of the tablet formed by the negative electrode material under different pressures.
[0037] In some preferred embodiments, the tableting orientation OI value y of the negative electrode material at different tableting densities satisfies: y 1 ≤y≤y 2 ; Among them, y 1 =5.46x-3.78,y 2 =8.88x-8.
[0038] In some preferred embodiments, the negative electrode material has a pressed sheet orientation OI value of 5 to 10, preferably 5 to 9, which can further improve the first coulombic efficiency and cycle stability of the negative electrode material.
[0039] The geometric morphology of the negative electrode material particles has a certain influence on the electrochemical performance and cycle stability. The geometric morphology of the particles will affect the contact area with the electrolyte and its mechanical stability during the charge and discharge process, thereby affecting the charge and discharge performance and cycle stability of the secondary battery. In some embodiments, the shape coefficient of the negative electrode material is φ, and the sphericity of the particles is Sh(90%), satisfying: Δ=|φ-Sh(90%)|, and Δ≤0.08; wherein, φ=D1 / D2, D1 is the D50 particle size of the negative electrode material, in μm; D2 is the equal volume average particle size of the negative electrode material, in μm. Specifically, Δ=|φ-Sh(90%)|, it can be understood that Δ is the absolute value of the difference between φ and Sh(90%). By limiting the shape coefficient φ of the negative electrode material and the sphericity Sh(90%) of the particles to satisfy the above relationship, it is possible to ensure excellent contact between the particles, while ensuring that the particles have good mechanical stability and can resist volume expansion and contraction, thereby improving the charge and discharge performance and cycle stability of the secondary battery. In some preferred embodiments, Δ≤0.06, which can further improve the charge and discharge performance and cycle stability.
[0040] Sphericity refers to the degree to which a particle is close to a sphere. The sphericity Sh (90%) of the negative electrode material refers to the ratio of the maximum diameter to the minimum diameter of the particle among 90% of the particles. The closer this ratio is to 1, the closer the particle is to a perfect sphere. In some embodiments, the sphericity Sh (90%) of the negative electrode material is 0.90~0.95, which means that most of the graphite particles have a high sphericity. In addition to helping to further improve the first coulomb efficiency and cycle stability of the secondary battery, this geometric form helps to form a denser structure during the compaction process, which helps to improve the energy density of the secondary battery. In addition, spherical graphite particles are isotropic and can form a more uniform lithium ion transmission path and a more stable conductive network. Compared with irregularly shaped particles, spherical particles are arranged more orderly in the electrode, which can reduce the electron and lithium ion transmission resistance inside the secondary battery and improve the charge and discharge rate and capacity of the secondary battery.
[0041] The D50 volume average particle size is the particle size corresponding to the cumulative volume distribution percentage in the sample reaching 50%, reflecting the average particle size of the negative electrode material. In some embodiments, the D50 volume average particle size of the negative electrode material is 8-18 μm. The equal volume average particle size refers to the average particle size of a sphere with the same average volume as the particle. In some embodiments, the equal volume average particle size of the negative electrode material is 10-20 μm. By limiting the D50 volume average particle size and the equal volume average particle size of the negative electrode material to a suitable range, in addition to further helping to improve the first coulomb efficiency and cycle stability of the secondary battery, the diffusion path of lithium ions can be shortened, and the transmission resistance of lithium ions during the insertion and deinsertion process can be reduced, thereby improving the charge and discharge efficiency. In addition, the internal pores of the electrode can be reduced, and the energy density of the secondary battery can be improved. In some preferred embodiments, the D50 volume average particle size of the negative electrode material is 10-18 μm, and the equal volume average particle size is 11-18 μm.
[0042] Specific surface area (SSA) refers to the total surface area per unit mass of a material. In some embodiments, the specific surface area of the negative electrode material is 2 to 5 m 2 / g. By limiting the specific surface area of the negative electrode material within a moderate range, in addition to further improving the initial coulombic efficiency and cycle performance, it can also provide a moderate diffusion path, which not only avoids the performance degradation caused by the electrolyte penetrating into the internal pores of the material, but also facilitates the rapid and uniform diffusion of lithium ions during the charge and discharge process, thereby improving the rate performance and cycle stability of the secondary battery. In addition, it can reduce the contact between the electrolyte and the surface of the graphite material, reducing the possibility of side reactions, such as electrolyte decomposition and co-embedding of solvent molecules.
[0043] Tap density (Tap) refers to the compactness of a material under physical vibration. In some embodiments, the tap density of the negative electrode material is 0.9~1.3g / cm 3. By limiting the tap density of the negative electrode material within a moderate range, it helps to improve the compaction density of the material during the electrode manufacturing process, reduce the internal pores of the electrode, improve the utilization rate of the negative electrode material and the energy density of the secondary battery, and at the same time reduce the contact area between the electrolyte and the graphite particles, thereby reducing the formation of the SEI film, reducing the irreversible capacity during the first charge and discharge, and improving the first coulomb efficiency; it also helps to reduce the volume expansion during the cycle, reduce the mechanical stress between the particles, and prevent the formation of cracks, thereby improving the cycle stability. In addition, it helps to maintain the integrity of the electrode structure, prevent the active material from falling off the current collector, and further improve the cycle performance. In some preferred embodiments, the tap density of the negative electrode material is 1~1.3g / cm 3 .
[0044] The powder compaction density refers to the density of the negative electrode material powder under a certain pressure (e.g. 2T), which is usually determined by compacting the material under a certain pressure and then measuring the volume and mass of the material after compaction. The powder compaction density is directly related to the energy density, first coulomb efficiency and cycle stability of the secondary battery. In some embodiments, the powder compaction density of the negative electrode material is 1.7~2.0g / cm 3 By limiting the compaction density of the powder within an appropriate range, the graphite particles can be brought into closer contact, which helps to form a more uniform and stable SEI film, thereby further improving the initial coulombic efficiency. At the same time, the relative movement between particles is reduced, and the mechanical stress on the graphite particles during the charge and discharge cycle is reduced, thereby further improving the cycle stability. In addition, the negative electrode material can be distributed more evenly, which helps to improve the energy density.
[0045] The negative electrode material of the present invention can be used as a negative electrode material in a secondary battery, and can effectively improve the initial coulombic efficiency and cycle stability of the secondary battery. For example, in some embodiments, the initial coulombic efficiency of the negative electrode material is above 94%, and the 400-week capacity retention rate is ≥92.5%. The capacity is ≥360mAh / g.
[0046] The present invention does not limit the specific preparation process of the negative electrode material, as long as the above parameters are met. In some embodiments, the preparation method of the negative electrode material includes the following steps:
[0047] S1, oxidizing the graphite raw material to obtain graphite oxide;
[0048] S2, sequentially mixing and coating graphite oxide and asphalt, and subjecting them to a first heat treatment to obtain a composite;
[0049] S3, performing a densification treatment on the composite to obtain an intermediate product;
[0050] S4, subjecting the intermediate product to a second heat treatment to obtain a negative electrode material.
[0051] Specifically, in S1, the graphite raw material is oxidized to effectively improve the surface activity of the graphite raw material, which not only promotes the uniformity in the subsequent coating process, but also helps to improve the compatibility and stability of the material with the electrolyte, so as to achieve mechanical properties matching the insertion / deinsertion of lithium ions.
[0052] The specific temperature, gas content and time of the oxidation treatment can be adjusted according to actual conditions. For example, in some embodiments, the graphite raw material can be natural graphite, and the natural graphite can be spherical graphite, and the D50 volume average particle size of the spherical graphite is 1-20 μm. This particle size range can ensure the uniformity and stability of the material in the subsequent processing process; the oxidation treatment can be carried out under the condition of an oxygen volume content of 1% to 10%, the oxidation treatment temperature is 400-600°C, and the time is 2-3 hours.
[0053] In S2, the graphite oxide is mixed and coated with asphalt. It can be understood that the graphite oxide and asphalt are mixed at room temperature. During the mixed coating process, the asphalt and the graphite oxide are evenly mixed to obtain a mixture; the mixture is subjected to a first heat treatment so that the molten asphalt fills the pores inside the graphite to obtain a composite. The mixed coating and the first heat treatment help to improve the density, compactness and hardness of the material.
[0054] The specific mixing ratio of graphite oxide and asphalt can be adjusted according to material properties and requirements. For example, in some embodiments, the mass ratio of graphite raw material to asphalt is 100: (1~30); the asphalt is selected from at least one of petroleum asphalt, coal asphalt, and intermediate phase asphalt, and the D50 volume average particle size of the asphalt is 2~3μm; the softening point of the asphalt is 100~300℃, and the mixing coating time is 10~60min; the first heat treatment can be carried out in a first inert atmosphere at a temperature higher than the softening point of the asphalt; the first inert atmosphere is to prevent oxidation of the material during the heat treatment process, and any inert gas can achieve this purpose, for example, it can include at least one of nitrogen, helium, and argon; the temperature of the first heat treatment is 200~600℃, and the time is 3~4h.
[0055] In S3, the densification treatment includes a profiling treatment and an isostatic pressing treatment. Specifically, the composite is firstly profiling with a hydraulic press to obtain a profiling product; then the profiling product is isostatically pressed to obtain an isostatically pressed product; and finally the isostatically pressed product is crushed to obtain an intermediate product. The densification treatment can effectively reduce the internal pores of the graphite, increase the density of the material, enhance its structural density, and improve the pore filling effect, so that the particle hardness and elastic modulus of the material meet the above requirements.
[0056] The specific pressure, time, and number of cycles of the profiling treatment can be adjusted according to the actual equipment capacity and material requirements. For example, in some embodiments, the profiling conditions are: the pressure of the hydraulic press is 10~40MPa, the holding time is 0~2min, and the pressure is released for 0.5min before slowly reciprocating 2~4 times. The short holding time can ensure that the material quickly forms a dense structure under high pressure, while avoiding equipment wear and reduced production efficiency caused by long-term holding pressure. It is suitable for continuous production processes and can improve production efficiency and equipment utilization. Isostatic pressing can further improve the density and structural stability of the material, and the specific pressure and time can be optimized according to the performance requirements of the material and the equipment capacity. For example, in the isostatic pressing treatment, the filling effect of asphalt inside the graphite can be regulated by adjusting the pressure. For example, the isostatic pressing treatment can adopt cold isostatic pressing or warm isostatic pressing. The pressure of the isostatic pressing treatment is 60~120MPa, and the holding time is 1~60min.
[0057] In S4, the intermediate product is subjected to a second heat treatment under a second inert atmosphere to ensure the graphitization degree of the material. After the second heat treatment, the negative electrode material is obtained after being dispersed, demagnetized and sieved. The second heat treatment converts the asphalt into amorphous carbon to ensure that the material is stably carbonized at high temperature and improve its graphitization degree. The appropriate heat treatment temperature and time can affect the crystallinity and microstructure of the graphite, so that its hardness and elastic modulus meet the above requirements.
[0058] The specific temperature and time of the second heat treatment can be adjusted according to the conditions of the heat treatment device and the performance target of the material. For example, in some embodiments, the temperature of the second heat treatment is greater than the temperature of the first heat treatment, for example, the temperature of the second heat treatment is 900~1600℃, and the time is 10~24h. Among them, the second inert atmosphere is to prevent oxidation of the material during the heat treatment process, and any inert gas can achieve this purpose, for example, it can include at least one of nitrogen, helium, and argon.
[0059] A second aspect of the present invention provides a negative electrode sheet, which includes the negative electrode material provided by the first aspect.
[0060] The negative electrode sheet of the present invention comprises a negative electrode current collector and a negative electrode material active layer disposed on at least one surface of the negative electrode current collector. The negative electrode material active layer comprises the negative electrode material provided in the first aspect. The negative electrode current collector may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, and may also be a composite current collector disclosed in any prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate. Since the negative electrode sheet comprises a negative electrode material with excellent performance, the application of the negative electrode sheet in a secondary battery helps to improve the first coulomb efficiency and cycle stability of the secondary battery.
[0061] The negative electrode material active layer also includes a binder to bind the negative electrode active material particles to facilitate the formation of a film layer, and can also improve the binding force between the negative electrode material active layer and the negative electrode current collector. In some embodiments, the binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic (ester) styrene butadiene rubber, epoxy resin or nylon, etc.
[0062] The negative electrode material active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0063] When preparing the negative electrode sheet, the negative electrode material, the conductive agent and the binder can be dispersed in an appropriate amount of solvent, and the mixture is stirred and mixed to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and cutting. In a specific embodiment, the negative electrode active layer includes 70% to 99% of the negative electrode material, 0.5% to 15% of the conductive agent, and 0.5% to 15% of the binder in terms of mass percentage.
[0064] The conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene; the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyvinyl alcohol, and sodium polyacrylate. In a third aspect of the present invention, a secondary battery is provided, the secondary battery comprising the negative electrode sheet provided in the second aspect.
[0065] Due to the inclusion of the above-mentioned negative electrode sheet with excellent performance, the secondary battery has excellent first coulombic efficiency and cycle stability.
[0066] Specifically, the secondary battery includes a housing, an electrode assembly and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.
[0067] The outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), for example, a soft-pack battery. In other embodiments, it may also be a steel shell battery, an aluminum shell battery, etc.
[0068] See also Figure 3 and Figure 4 The electrode assembly 100 includes a positive electrode sheet 101, a negative electrode sheet 102 and a separator 103, wherein the separator 103 is disposed between the positive electrode sheet 101 and the negative electrode sheet 102. Figure 3 , active ions (such as lithium ions) are deintercalated from the lattice of the positive electrode material (such as the lithiated intercalation compound) of the positive electrode sheet 101, pass through the separator 103 through the electrolyte, reach the negative electrode sheet 102 and insert into the lattice of the negative electrode material. Figure 4 , active ions (such as lithium ions) are deintercalated from the lattice of the negative electrode material of the negative electrode sheet 102, pass through the isolation membrane 103 through the electrolyte, reach the positive electrode sheet 101 and are embedded in the lattice of the positive electrode material (such as the lithiated intercalation compound), generating electrons that travel from the negative electrode sheet 102 through the external circuit to the positive electrode sheet 101, and the reverse movement of the electrons forms an electric current that can be used by electrical appliances.
[0069] In some embodiments, the electrode assembly 100 may be a laminated structure, which is formed by alternately stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102. In other embodiments, the electrode assembly 100 may also be a wound structure, which is formed by stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102 in sequence and then winding them.
[0070] The positive electrode sheet 101 includes a positive electrode current collector and a positive electrode material active layer provided on at least one surface of the positive electrode current collector. The positive electrode current collector may be made of aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate. The positive electrode material active layer includes a positive electrode active material, and the positive electrode active material includes a compound that reversibly embeds and deintercalates lithium ions (i.e., a lithiated intercalation compound). In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO 2 ), lithium nickel manganese cobalt ternary materials (NCM), lithium manganese oxide (LiMn 2 O 4 ), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O 4 ) or lithium iron phosphate (LiFePO 4 ) at least one of the following.
[0071] The positive electrode material active layer also includes a binder to bond the positive electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the bonding force between the positive electrode material active layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon.
[0072] The positive electrode material active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0073] The isolation membrane 103 includes a membrane layer with a porous structure, and its material includes but is not limited to at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, the isolation membrane 103 can be a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite membrane.
[0074] The electrolyte has the function of conducting ions between the positive electrode sheet 101 and the negative electrode sheet 102. The electrolyte can be in one or more of a gel state, a solid state, and a liquid state. In some embodiments, the electrolyte is an electrolyte. The electrolyte plays a role in conducting active ions between the positive electrode sheet 101 and the negative electrode sheet 102. In some embodiments, the electrolyte includes a lithium salt and an organic solvent. The lithium salt can be selected from, but is not limited to, lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ) and lithium hexafluoroarsenate (LiAsF 6 ), lithium perchlorate (LiClO 4 )、lithium tetraphenylborate(LiB(C 6 H 5 ) 4 ), lithium methanesulfonate (LiCH 3 SO 3 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF 3 SO 3 )、Lithium bis(trifluoromethylsulfonyl)imide(LiN(SO2 CF 3 ) 2 ), tris(trifluoromethylsulfonyl)methyllithium (LiC(SO 2 CF 3 ) 3 ), lithium bis(oxalatoborate) (LiBOB) and lithium difluorophosphate (LiPO 2 F 2 ) one or more. For example, the lithium salt is LiPF 6 The organic solvent may be a carbonate compound, a carboxylate compound, an ether compound, a nitrile compound, other organic solvents or a combination thereof. Examples of carbonate compounds include, but are not limited to, diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethylmethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, or combinations thereof.
[0075] When preparing secondary batteries, the positive electrode sheets, separators and negative electrode sheets are wound or stacked to obtain battery cells, which are then packaged in pre-stamped aluminum-plastic films. After the packaged batteries are dried to remove moisture, the electrolyte is injected into the dry batteries. After aging, formation and secondary sealing of the batteries, the preparation of the secondary batteries is completed.
[0076] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0077] Example 1
[0078] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0079] S1, keeping 20 kg of graphite raw material (D50 volume average particle size of 16 μm) at 500° C. and 5% oxygen volume content for 3 h, cooling to room temperature, and obtaining graphite oxide;
[0080] S2, adding graphite oxide and 2.2 kg of petroleum asphalt (softening point is 250°C) into a VC mixer and mixing for 25 min. After uniform mixing, heat treatment is performed at 400°C for 4 h in a nitrogen atmosphere, and then cooled to room temperature to obtain a composite.
[0081] S3, the composite is subjected to densification treatment, and is subjected to a press process in a hydraulic press, with a pressure of 30 MPa, a holding time of 0.5 min, and two reciprocating cycles, and then subjected to an isostatic pressing densification treatment, with a maximum isostatic pressing pressure of 70 MPa, and after holding the pressure for 3 min, the composite is crushed to obtain an intermediate product;
[0082] S4, carbonizing the intermediate product at 1250° C. for 16 h under a nitrogen atmosphere, breaking it up, demagnetizing it, and sieving it to obtain the negative electrode material of this embodiment.
[0083] Example 2
[0084] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0085] S1, keeping 20 kg of graphite raw material (D50 volume average particle size of 16 μm) at 450°C and 6% oxygen content for 3 hours, cooling to room temperature, and obtaining graphite oxide;
[0086] S2, graphite oxide and 2.2 kg coal tar pitch (softening point 180°C) were added into a VC mixer and mixed for 25 min. After uniform mixing, the mixture was heat treated at 350°C for 4 h in a nitrogen atmosphere. After cooling to room temperature, a composite was obtained.
[0087] S3, the composite is subjected to densification treatment, and is pressed in a hydraulic press with a pressure of 20 MPa and a holding time of 0.5 min, and is reciprocated twice, and then is subjected to isostatic pressing densification treatment with a maximum isostatic pressing pressure of 70 MPa. After holding the pressure for 3 min, the composite is crushed to obtain an intermediate product;
[0088] S4, carbonizing the intermediate product at 1250° C. for 14 h under a nitrogen atmosphere, breaking it up, demagnetizing it, and sieving it to obtain the negative electrode material of this embodiment.
[0089] Example 3
[0090] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0091] S1, 20 kg of graphite raw material (D50 volume average particle size is 16 μm) is kept at a temperature of 500°C and an oxygen content of 6% for 3 hours, and then cooled to room temperature to obtain graphite oxide;
[0092] S2, graphite oxide and 1.6 kg coal tar pitch (softening point 180°C) were added into a VC mixer and mixed for 25 min. After uniform mixing, the mixture was heat treated at 350°C for 3 h in a nitrogen atmosphere. After cooling to room temperature, a composite was obtained.
[0093] S3, the composite is subjected to densification treatment, and is pressed in a hydraulic press with a pressure of 20 MPa and a holding time of 0.5 min, and is reciprocated twice, and then is subjected to isostatic pressing densification treatment with a maximum isostatic pressing pressure of 60 MPa. After holding the pressure for 3 min, the composite is crushed to obtain an intermediate product;
[0094] S4, carbonizing the intermediate product at 1250° C. for 12 h under a nitrogen atmosphere, breaking it up, demagnetizing it, and sieving it to obtain the negative electrode material of this embodiment.
[0095] Example 4
[0096] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0097] S1, 20 kg of graphite raw material (D50 volume average particle size is 14.5 μm) is kept at a temperature of 500°C and an oxygen content of 5% for 3 hours, and then cooled to room temperature to obtain graphite oxide;
[0098] S2, graphite oxide and 2.2 kg petroleum asphalt (softening point 250°C) were added into a VC mixer and mixed for 25 min. After uniform mixing, the mixture was heat treated at 400°C for 4 h under a nitrogen atmosphere. After cooling to room temperature, a composite was obtained.
[0099] S3, the composite is subjected to densification treatment, and is pressed in a hydraulic press with a pressure of 30 MPa, a holding time of 0.5 min, and reciprocated twice, and isostatically densified with a maximum isostatic pressure of 70 MPa. After holding the pressure for 3 min, the composite is crushed to obtain an intermediate product;
[0100] S4, carbonizing the intermediate product at 1250° C. for 16 h under a nitrogen atmosphere, breaking it up, demagnetizing it, and sieving it to obtain the negative electrode material of this embodiment.
[0101] Example 5
[0102] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0103] S1, 20 kg of graphite raw material (D50 volume average particle size is 10 μm) is kept at a temperature of 550°C and an oxygen content of 5% for 3 hours, and then cooled to room temperature to obtain graphite oxide;
[0104] S2, graphite oxide and 2.2 kg petroleum asphalt (softening point 250°C) were added into a VC mixer and mixed for 25 min. After uniform mixing, the mixture was heat treated at 400°C for 4 h under a nitrogen atmosphere. After cooling to room temperature, a composite was obtained.
[0105] S3, the composite is subjected to densification treatment, and is pressed in a hydraulic press with a pressure of 30 MPa and a holding time of 0.5 min, and is reciprocated twice, and then is subjected to isostatic pressing densification treatment with a maximum isostatic pressing pressure of 70 MPa. After holding the pressure for 3 min, the composite is crushed to obtain an intermediate product;
[0106] S4, carbonizing the intermediate product at 1250° C. for 16 h under a nitrogen atmosphere, breaking it up, demagnetizing it, and sieving it to obtain the negative electrode material of this embodiment.
[0107] Example 6
[0108] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0109] S1, 20kg of graphite raw material (D50 volume average particle size is 16μm) is pressed in a hydraulic press with a pressure of 40MPa, holding pressure for 0.5min, and reciprocating for 3 times. After pressing, it is crushed to an average particle size of 16μm, and then isostatic pressing densification treatment is performed with a maximum isostatic pressing pressure of 80MPa. After holding pressure for 3min, it is crushed to obtain an intermediate product;
[0110] S2, the intermediate product and 2.2 kg of asphalt (softening point 250°C) are added to a VC mixer and mixed for 25 minutes. After uniform mixing, the mixture is carbonized at 1250°C for 16 hours under a nitrogen atmosphere. After carbonization, the negative electrode material of this comparative example is obtained by breaking up, demagnetizing and sieving.
[0111] Example 7
[0112] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0113] S1, 20kg of graphite raw material (D50 volume average particle size is 16μm) is pressed in a hydraulic press with a pressure of 30MPa, holding pressure for 0.5min, and reciprocating for 3 times. After pressing, it is crushed to an average particle size of 16μm, and then isostatic pressing densification treatment is performed with a maximum isostatic pressing pressure of 100MPa. After holding pressure for 3min, it is crushed to obtain an intermediate product;
[0114] S2, the intermediate product and 2.2 kg of asphalt (softening point 250°C) are added to a VC mixer and mixed for 25 minutes. After uniform mixing, the mixture is carbonized at 1250°C for 18 hours under a nitrogen atmosphere. After carbonization, the negative electrode material of this comparative example is obtained by breaking up, demagnetizing and sieving.
[0115] Comparative Example 1
[0116] The preparation method of the negative electrode material of this comparative example comprises the following steps:
[0117] 20 kg of graphite raw material (D50 volume average particle size is 16 μm) and 2.2 kg of asphalt (softening point 250°C) were added to a VC mixer and mixed for 25 minutes. After mixing, the materials were carbonized at 1250°C for 16 hours under a nitrogen atmosphere. After carbonization, the negative electrode material of this comparative example was obtained by breaking up, demagnetizing and sieving.
[0118] Comparative Example 2
[0119] The preparation method of the negative electrode material of this comparative example comprises the following steps:
[0120] 20 kg of graphite raw material (D50 volume average particle size is 10 μm) and 2.2 kg of asphalt (softening point 250°C) were added to a VC mixer and mixed for 25 minutes. After mixing, the materials were carbonized at 1250°C for 16 hours under a nitrogen atmosphere. After carbonization, the negative electrode material of this comparative example was obtained by breaking up, demagnetizing and sieving.
[0121] Comparative Example 3
[0122] The preparation method of the negative electrode material of this comparative example comprises the following steps:
[0123] S1, 20 kg of graphite raw material (D50 volume average particle size of 16 μm) and 1.4 kg of petroleum asphalt (softening point of 120°C) were added into a VC mixer and mixed for 25 min. After uniform mixing, the mixture was heat treated at 400°C for 4 h under a nitrogen atmosphere, and cooled to room temperature to obtain a composite.
[0124] S2, the composite is subjected to densification treatment, and is pressed in a hydraulic press with a pressure of 20 MPa and a holding time of 0.5 min, and is reciprocated twice, and then is subjected to isostatic pressing densification treatment with a maximum isostatic pressing pressure of 50 MPa, and is crushed after holding the pressure for 3 min to obtain an intermediate product;
[0125] S3, carbonizing the intermediate product at 1250° C. for 14 h under a nitrogen atmosphere, breaking up, demagnetizing and sieving after carbonization to obtain the negative electrode material of this comparative example.
[0126] Comparative Example 4
[0127] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0128] S1, 20kg of graphite raw material (D50 volume average particle size is 16μm) is pressed in a hydraulic press with a pressure of 30MPa, holding pressure for 0.5min, and reciprocating for 3 times. After pressing, it is crushed to an average particle size of 16μm, and then isostatic pressing densification treatment is performed with a maximum isostatic pressing pressure of 120MPa. After holding pressure for 3min, it is crushed to obtain an intermediate product;
[0129] S2, the intermediate product and 2.2 kg of asphalt (softening point 180°C) are added to a VC mixer and mixed for 25 minutes. After uniform mixing, the mixture is carbonized at 1250°C for 14 hours under a nitrogen atmosphere. After carbonization, the negative electrode material of this comparative example is obtained by breaking up, demagnetizing and sieving.
[0130] Test example
[0131] 1. Particle hardness (HIT) and elastic modulus (EIT) test
[0132] The particle hardness (HIT) and elastic modulus (EIT) of the negative electrode material were tested using the Anton Paar NHT2 nanoindenter. The negative electrode material was placed on the sample stage of the indenter, and the static displacement mode was adopted. The glassy triangular pyramid indenter was used. The indenter contacted the sample and recorded at a set rate until the set indentation depth was 1200nm. After reaching the set depth, the load time was maintained for 15s, and then the load was unloaded at the same rate, where the loading and decompression rate was 5mN / min and the Poisson's ratio was 0.3. The particle hardness was calculated according to the indentation depth and load size, and the elastic modulus was calculated according to the slope of the fitting line of 40~98% of the unloading curve. 10 particles were measured for each sample, and the average value was taken after the test.
[0133] 2. Tablet orientation test
[0134] The negative electrode material, carboxymethyl cellulose solution and styrene butadiene rubber solution were mixed in a mass ratio of 19.3:25:0.8, wherein the concentration of styrene butadiene rubber in the styrene butadiene rubber solution was 50wt%, and the concentration of carboxymethyl cellulose in the carboxymethyl cellulose solution was 1.2wt%. The slurry was evenly dispersed using a high-speed disperser; the slurry was evenly coated on the surface of the aluminum foil, and then placed in a constant temperature drying oven at a temperature of 80~95℃ and baked for more than 6 hours until the slurry was completely dry to obtain a sample to be tested; after the sample to be tested was ground through 200 mesh, a tablet press was used to apply pressure to the sample to be tested at a pressure of 0.5T (ton), 1T (ton) and 2T (ton) to obtain a sheet sample (pressed tablet); the pressed tablet was placed under a thickness gauge to obtain the initial thickness of the pressed tablet after 10s, and then the pressed tablet was placed in a constant temperature environment (25±3℃) for 16 hours, and the thickness was measured by 1000 μm. The thickness of the tablet after rebound (after standing for 16 hours) was measured with a ruler, and the compaction density of the tablet under the corresponding pressure was calculated based on the tablet mass, initial thickness and thickness after rebound; the tablet was analyzed using an X-ray diffractometer to obtain the crystal structure and orientation; the crystal plane orientation and the corresponding peak area were obtained by analyzing the X-ray diffraction spectrum, and the OI value was calculated according to the tablet orientation OI value = I004 / I110, where I004 is the diffraction peak area of the (004) crystal plane in the X-ray diffraction spectrum, and I110 is the diffraction peak area of the (110) crystal plane in the X-ray diffraction spectrum. The test results can be seen Figure 2 and Table 1, in which x represents the tablet compaction density, y represents the tablet orientation OI value, Figure 2 In the table, X represents the compacted density and Y represents the tablet orientation OI value.
[0135] 3. Particle size test
[0136] The Malvern 3000 laser particle size analyzer was used to test the D50 volume average particle size (D1) and the equal volume average particle size D2 of the negative electrode material. The sample, a small amount of dispersant (a mixture of ethanol, pure water and low-foaming surfactant) and pure water were added to a 50 mL beaker. The sample was fully stirred with a glass rod to make the sample evenly dispersed. The sample was transferred to the sample cell of the Malvern 3000 laser particle size analyzer, and the pump speed of the equipment was set to 2400~2500 r / min and the frequency was set to 19.5 Hz for particle size testing.
[0137] 4. Sphericity Sh (90%) test
[0138] The sphericity of the negative electrode material was tested using SYMPATEC's QICPIC dynamic particle image analyzer. Sh(90%) refers to the ratio of the maximum diameter to the minimum diameter of the particles among 90% of the particles.
[0139] 5. Specific surface area SSA test
[0140] The JW-DX dynamic specific surface area measuring instrument is used to test the specific surface area of the negative electrode material. Based on the relevant theories of physical adsorption, the continuous flow method proposed by Nelsen and Eggertsen is used as the structure to determine the specific surface area of the solid. A mixed gas with hydrogen as the carrier and nitrogen as the adsorption gas is passed into the sample tube. When the sample tube is immersed in liquid nitrogen to reach a low temperature environment, the nitrogen in the mixed gas will be physically adsorbed by the sample until the adsorption is saturated. At this time, the proportion of nitrogen in the mixed gas will change. During the adsorption process, the high-precision thermal conductivity detection instrument will complete the detection and calculation work.
[0141] 6. Tap density test
[0142] The tap density of the negative electrode material was tested using the Quantachrome Dual Autotap device. 100 mL of the negative electrode material sample was placed in a measuring cylinder and mechanically vibrated 1000 times. The sample mass and volume after tapping were obtained, and the tap density was calculated according to the formula: tap density (g / cm³) = sample mass / volume after tapping.
[0143] 7. Powder compaction density test
[0144] Introduce 1.0±0.05g of negative electrode material into the metal sleeve, and place the sleeve loaded with the sample in the center of the compaction density meter CARVER 4350.22. Slowly apply pressure to 2T (tons), stop further pressurization, start the second hand, maintain the pressure for 30s and then quickly remove the pressure. Take the sample out of the metal mold cavity and place it on the horizontal workbench on the thickness gauge. Use a thickness ruler to measure the height after compaction, and calculate the powder compaction density according to the powder compaction density (g / cm³) = sample mass / volume after compaction.
[0145] 8. First Coulomb efficiency test
[0146] The negative electrode materials of the embodiment and the comparative example, carboxymethyl cellulose and styrene-butadiene rubber were dissolved in pure water at a mass ratio of 96.5:1.5:2, and the solid content was controlled to be 50% to obtain a negative electrode slurry; the negative electrode slurry was coated on a copper foil current collector, and after vacuum drying at 95° C., roller pressing and pressurizing, a negative electrode sheet was obtained; a metal lithium sheet was used as a counter electrode, and a button battery was assembled in a glove box filled with argon.
[0147] The button cell was charged and discharged at a current density of 0.1C in the charge and discharge range of 0.01~1.5V to obtain the first reversible specific capacity, first cycle charging capacity and first cycle discharge capacity. The first coulombic efficiency was calculated according to the first coulombic efficiency = first cycle discharge capacity / first cycle charging capacity.
[0148] 9. Cycle stability test
[0149] Large single crystal nickel cobalt manganese oxide (NCM523) is mixed with conductive carbon black and PVDF in a mass ratio of 94:3.0:3.0, dissolved in N-methylpyrrolidone, and the solid content is controlled to be 50% to obtain a positive electrode slurry; the positive electrode slurry is coated on an aluminum foil current collector, and after vacuum drying at 95°C, roller pressing, and pressurization, a positive electrode sheet is obtained;
[0150] The negative electrode materials of the embodiment and the comparative example, carboxymethyl cellulose, styrene-butadiene rubber and conductive carbon black were dissolved in N-methylpyrrolidone at a mass ratio of 95:1.5:2.1:1.2, respectively, and the solid content was controlled to be 50% to obtain a negative electrode slurry; the negative electrode slurry was coated on a copper foil current collector, and after vacuum drying at 95° C., roller pressing and pressurizing, a negative electrode sheet was obtained;
[0151] The positive electrode sheet, separator and negative electrode sheet are assembled into a lithium-ion battery, and the electrolyte is injected to obtain a soft-pack battery of about 40mAh; the electrolyte is 1mol / L LiPF 6 / ethylene carbonate (EC) + propylene carbonate (PC) + diethyl carbonate (DEC) + EMC (volume ratio 1:0.3:1:1), the diaphragm is a PP / PE / PP three-layer composite diaphragm.
[0152] The above soft pack battery was used to test the cycling performance of the material. It was charged to 4.20V at a constant current with a charge rate of 1C, then charged at a constant voltage, the current gradually decreased to 0.05C, and then discharged to 2.75V at a discharge rate of 1C. This charge and discharge cycle was repeated 400 times, and the discharge capacity Q1 at the first cycle and the discharge capacity Q400 at the 400th cycle were measured. The 400-week capacity retention rate was calculated according to the 400-week capacity retention rate = Q400 / Q1×100%.
[0153] The test results are shown in Table 1 and Table 2.
[0154] Table 1
[0155]
[0156] Table 2
[0157]
[0158] In Table 2, D1 is the D50 volume average particle size of the negative electrode material, and D2 is the equal volume average particle size of the negative electrode material.
[0159] According to Table 1, Table 2 and Figure 1 , Figure 2It can be seen that the negative electrode materials of Examples 1 to 7 all meet the requirements of particle hardness of 0.28 GPa to 0.4 GPa, elastic modulus of 7.0 GPa to 8.0 GPa, and tablet orientation OI value of y, 4<y≤11, while the negative electrode materials of Comparative Example 1 do not meet the requirements of particle hardness of 0.28 GPa to 0.4 GPa, elastic modulus of 7.0 GPa to 8.0 GPa, and tablet orientation OI value of y, 4<y≤11; the negative electrode material of Comparative Example 2 does not meet the requirements of elastic modulus of 7.0 GPa to 8.0 GPa, the negative electrode material of Comparative Example 3 does not meet the requirements of particle hardness of 0.28 GPa to 0.4 GPa, and the negative electrode material of Comparative Example 4 has a compaction density of 1.61 g / cm 3 When the range of the OI value of the tableting orientation is not satisfied, the first coulombic efficiency of Examples 1 to 7 is higher than that of Comparative Examples 1 to 4, the expansion performance is improved, the 400-cycle capacity retention rate is high, and the overall electrical performance is good. It can be seen that the present invention can significantly improve the first coulombic efficiency and cycle stability by making the material meet the particle hardness of 0.28GPa to 0.4GPa, the elastic modulus of 7.0GPa to 8.0GPa, and the tableting orientation OI value of y, 4<y≤11.
[0160] Furthermore, compared with Examples 6 to 7, the negative electrode materials of Examples 1 to 5 satisfy the following relationship: the OI values of the tablet orientation are all within the range of y under different tablet compaction densities, while satisfying the particle hardness of 0.28 GPa to 0.4 GPa, the elastic modulus of 7.0 GPa to 8.0 GPa, and the tablet orientation OI value is y, 4<y≤11. 1 ≤y≤y 2 In the range, and y 1 =5.46x-3.78,y 2 =8.9x-7.76, the densification degree of the negative electrode material is further improved, and the structural stability is also further improved, so that the first coulombic efficiency of the negative electrode materials of Examples 1-5 is above 94%, the expansion performance is improved, and the 400-week capacity retention rate is ≥92.5%, which is better than Examples 6-7.
[0161] Furthermore, compared with Example 3, the negative electrode materials of Examples 1, 2, and 4 satisfy the particle hardness of 0.28 GPa to 0.4 GPa, the elastic modulus of 7.0 GPa to 8.0 GPa, the tablet orientation OI value of y, 4 < y ≤ 11, and the tablet orientation OI value of y at different tablet compaction densities. 1 ≤y≤y 2 In the range, and y 1 =5.46x-3.78,y 2=8.9x-7.76, the negative electrode materials of Examples 1, 2 and 4 further meet the following requirements: the OI value of the tablet orientation is 5-9, the filling rate and the structural stability of the negative electrode materials are further improved, and the volume expansion of the material is further alleviated, so that the first coulombic efficiency of the negative electrode materials of Examples 1, 2 and 4 are all above 94.84%, and the capacity retention rate of 400 weeks is ≥93.98%, which is better than that of Example 3.
[0162] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A negative electrode material, characterized in that: The negative electrode material comprises natural graphite and amorphous carbon filled in the pores of the natural graphite; the particle hardness of the negative electrode material is 0.28GPa~0.4GPa, and the elastic modulus is 7.0GPa~8.0GPa; when the compaction density of the negative electrode material is 1.5~2.0g / cm 3 When the negative electrode material is pressed, its tablet orientation OI value is y, 4<y≤11.
2. The negative electrode material according to claim 1, characterized in that The tablet orientation OI value y of the negative electrode material at different compaction densities satisfies the following condition: y1≤y≤y2; Among them, y1=5.46x-3.78, y2=8.9x-7.76, 1.5≤x≤2.0, and x is the value corresponding to the compaction density of the negative electrode material.
3. The negative electrode material according to claim 1, characterized in that When the compaction density of the negative electrode material is 1.5-2.0 g / cm 3 , the OI value y of the negative electrode material's pressed sheet orientation is 5~10.
4. The negative electrode material according to claim 1 or 2, characterized in that: The negative electrode material meets at least one of the following characteristics: (1) The sphericity Sh (90%) of the negative electrode material is 0.90-0.95; (2) The D50 volume average particle size of the negative electrode material is 8 to 18 μm; (3) The average particle size of the negative electrode material is 10-20 μm.
5. The negative electrode material according to claim 4, characterized in that The shape coefficient φ of the negative electrode material and the sphericity Sh(90%) of the particles satisfy the following relationship: Δ=|φ-Sh(90%)|, and Δ≤0.08; wherein φ=D1 / D2, D1 is the D50 volume average particle size of the negative electrode material, in μm; and D2 is the equal volume average particle size of the negative electrode material, in μm.
6. The negative electrode material according to claim 1 or 2, characterized in that: The specific surface area of the negative electrode material is 2 to 5 m 2 / g.
7. The negative electrode material according to claim 1 or 2, characterized in that: The tap density of the negative electrode material is 0.9-1.3 g / cm 3 .
8. The negative electrode material according to claim 1 or 2, characterized in that: The powder compaction density of the negative electrode material is 1.7-2.0 g / cm 3 .
9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the negative electrode material according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: The secondary battery comprises the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Negative electrode active material for lithium ion secondary battery and lithium ion secondary battery
CN104247107A
Modified graphite material, graphite negative electrode material, preparation method of modified graphite material, preparation method of graphite negative electrode material and lithium battery
CN111740082A
Electrochemical device and electronic device
CN118198275A
Negative electrode active material for rechargeable lithium battery, method for preparing the same, negative electrode including the same, and rechargeable lithium battery including the negative electrode
KR1020140140952A
Anode for Lithium Secondary Battery, Lithium Secondary Battery Including the Same and Method of Fabricating the Same
US20220336810A1
Cited By
Negative electrode material, negative electrode sheet and secondary battery
WO2026098728A1
Negative electrode active material, secondary battery and electronic apparatus
WO2026183850A1
Negative electrode active material and preparation method therefor, negative electrode sheet, battery, and electric device
WO2026189044A1